Comparing the performance of English mental health providers in achieving patient outcomes. (September 2015) - Moran, Valerie; Jacobs, Rowena
Abstract: Evidence on provider payment systems that incorporate patient outcomes is limited for mental health care. In England, funding for mental health care services is changing to a prospective payment system with a future objective of linking some part of provider payment to outcomes. This research examines performance of mental health providers offering hospital and community services, in order to investigate if some are delivering better outcomes. Outcomes are measured using the Health of the Nation Outcome Scales (HoNOS) – a clinician-rated routine outcome measure (CROM) mandated for national use. We use data from the Mental Health Minimum Data Set (MHMDS) – a dataset on specialist mental health care with national coverage – for the years 2011/12 and 2012/13 with a final estimation sample of 305, 960 observations with follow-up HoNOS scores. A hierarchical ordered probit model is used and outcomes are risk adjusted with independent variables reflecting demographic, need, severity and social indicators. A hierarchical linear model is also estimated with the follow-up total HoNOS score as the dependent variable and the baseline total HoNOS score included as a risk-adjuster. Provider performance is captured by a random effect that is quantified using Empirical Bayes methods. We find that worse outcomes are associated with severity and better outcomes with older age and social support. After adjusting outcomes for various risk factors, variations in performance are still evident across providers. This suggests that if the intention to link some element of provider payment to outcomes becomes a reality, some providers may gain financially whilst others may lose. The paper contributes to the limited literature on risk adjustment of outcomes and performance assessment of providers in mental health in the context of prospective activity-based payment systems. Highlights: A new payment system has been introduced for mental health providers in England. A part of provider payment may be linked to achieving better patient outcomes. We compare provider performance in relation to outcomes after risk-adjustment. Wide variations in outcomes are evident after controlling for risk factors. Providers with better outcomes may gain if a part of payment is linked to outcomes.